A rare case of collodion baby with ophthalmic involvement - Bhardwaj, U; Phougat, A; Dey, M; Raut, S; Srivastav, G; Gupta, Y (Nepalese Journal of Ophthalmology, 2012)
Background: Ichthyosis is an infrequent clinical entity worldwide (1:300,000 births). When diagnosed in a newborn, two forms can be identified: collodion baby and its most severe form, harlequin fetus or maligna keratoma. In both cases, clinical manifestations are thick and hard skin with deep splits. The splits are more prominent in the flexion areas. Case: We report a case of a 4- day-old baby who was referred to JNMC Eye OPD by the Pediatric Department of the JNMC. He was having severe bilateral ectropion of the upper lids and chemosis of conjuntiva, without corneal involvement. There was distortion of the pinna and peeling of the skin, more over the chest around the neck region and over the flexor aspect of limbs. Conclusion: Management of collodion baby requires a multi-disciplinary approach. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5874 NEPJOPH 2012; 4(1): 184-186